TELAAH MODEL PROJECT BASED LEARNING BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN LITERASI MATEMATIKA - Fitriani, Ika (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2023)
Mathematical literacy ability is an ability that is an important factor in carrying out learning activities. This ability consists of formulating, applying, and explaining mathematics in various contexts. In line with this, PISA has added components and indicators of mathematical literacy ability to its latest assessment. One of the innovations that can improve mathematical literacy skills is to use project-based learning or what is known as Project based learning (PjBL). In this model, students can explore, interpret, synthesize and search for information in completing the projects they are working on. This research is a qualitative research using the Systematic Literature Review (SLR) method by reviewing similar research that has the same goal. The research step consists of 4 stages, namely, classifying, identifying, collecting and analyzing similar research regarding the Project based learning model. The results of this study are that the geogebra-assisted PjBL learning model can be used as an innovation to improve mathematical literacy skills. In addition, Project based learning (PjBL) learning requires students to learn in practice through real experiences, not just learning in theory in class.